HUBUNGAN C-REACTIVE PROTEIN DENGAN PEMANJANGAN PROTHROMBIN TIME PADA PASIEN SIROSIS HATI YANG MENGALAMI PERDARAHAN SALURAN MAKANAN BAGIAN ATAS - Mariadi, IK; Wibawa, IDN; Purwadi, N; Suryadarma, IGA (journal of internal medicine; Vol. 12, No. 1 Januari 2011, 2012)
Bacterial infections are common complications in cirrhosis, and cause the systemic in! ammation process. The nature of the relationship between gastrointestinal bleeding and infection in cirrhosis has not been clari" ed. Infection is associated with failure to control variceal bleeding and early variceal rebleeding in these patients. Bacterial infections, and particularly endotoxemia, have been shown to activate the coagulation system and generally to interfere with hemostasis. We performed cross-sectional analytic study in cirrhosis patients with upper gastrointestinal bleeding to assess whether there are any association between in! ammation process (CRP) with defect in haemostatic system (prolongation in prothrombin time). Forty-nine patients were evaluated, 37 (75.5%) out of these were male and the rest were female. Ninteen out of this with in! ammation process and 30 without in! ammation process. Fourteen out of 19 patients (73.7%) in in! ammation group have prolongation on prothrombin time and 12 out of 30 patients (40%) in non in! ammation group have prolongation on prothrombin time. The difference of this proportion statistically signi" cant (Chi-square test X2: 5.29; p = 0.021). The CRP also have positive correlation with prolongation in prothrombin time (Spearman correlation R = 0.390; p = 0.006). In conclusion there is signi" cant association between CRP and prothrombin time in cirrhosis patients with upper gastrointestinal bleeding.
Keywords: in! ammation, CRP, prothrombin time